2023
DOI: 10.1126/sciadv.adi1744
|View full text |Cite
|
Sign up to set email alerts
|

Direct microwave energy input on a single cation for outstanding selective catalysis

Fuminao Kishimoto,
Tatsushi Yoshioka,
Ryo Ishibashi
et al.

Abstract: Microwave (MW)–driven catalytic systems are attracting attention not only as an aggressive electrification strategy of the chemical industry but also as creating a unique catalytic reaction field that conventional equilibrium heating cannot achieve. This study unlocked direct and selective heating of single alkali metal cations in the pores of aluminosilicate zeolites under MW. Selectively heated Cs + cations in FAU zeolite exhibited selective CH 4 combustion per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…HZSM-5 also facilitated BTX production using its 10-membering rings forming a channel that was highly size and shape selective to BTX. , As a result, sufficient heating at these channels can be beneficial towards BTX formation. In another instance, it was found that, under the influence of electromagnetic waves, the metal cation within the ZSM-5 framework exhibited vibrations which led to a temperature gradient within the catalyst channel . Several other works described yields equivalent to higher temperatures in the presence of MW-induced heating in a catalyst. , In our case, whilst plastic was found to be transparent to MW, the only available source of MW energy dissipation was the HZSM-5 channel.…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…HZSM-5 also facilitated BTX production using its 10-membering rings forming a channel that was highly size and shape selective to BTX. , As a result, sufficient heating at these channels can be beneficial towards BTX formation. In another instance, it was found that, under the influence of electromagnetic waves, the metal cation within the ZSM-5 framework exhibited vibrations which led to a temperature gradient within the catalyst channel . Several other works described yields equivalent to higher temperatures in the presence of MW-induced heating in a catalyst. , In our case, whilst plastic was found to be transparent to MW, the only available source of MW energy dissipation was the HZSM-5 channel.…”
Section: Resultsmentioning
confidence: 46%
“…In another instance, it was found that, under the influence of electromagnetic waves, the metal cation within the ZSM-5 framework exhibited vibrations which led to a temperature gradient within the catalyst channel. 43 Several other works described yields equivalent to higher temperatures in the presence of MW-induced heating in a catalyst. 44,45 In our case, whilst plastic was found to be transparent to MW, the only available source of MW energy dissipation was the HZSM-5 channel.…”
Section: Yield Alkanes Alkanes Concentration Gasmentioning
confidence: 99%
“…Zeolites, a group of crystalline aluminosilicates with microporous structures, are extensively used in various fields as catalysts, adsorbents, and ion exchangers. , Over 250 different zeolite framework structures with various pore sizes, cavities, and channel dimensionalities exist, and these differences significantly influence their performance in various applications. Additionally, factors such as the crystal size and morphology, the type of extra-framework cations, and the state of the crystal surfaces are crucial in determining the performance of zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…All peaks were observed in the chemical shift range corresponding to Q 4 (Si(−O−Si) 4 ). The peak of Q 4 species was split into four peaks corresponding to T4, T2, T3, and T1, arranged from the high-field to the low-field side. 85 The broadened peak observed around −102 ppm (see Figure S5 for an enlarged graph) was assigned to an overlap of Si sites neighboring Al (Q 4 (1Al)) and ones connected to defective silanol (Q 3 ).…”
mentioning
confidence: 99%
“…1) The anionic charge of zeolite framework caused by the substitution of Si with Al is balanced by various cations, which works as active sites in various chemical reactions. 2) Small-pore zeolites, such as CHA, AEI, KFI, and RHO zeolites, are a group of zeolites that is characterized by their 8-rings (8R) as their largest pores. 3),4) These zeolites are gaining much attention due to their remarkable catalytic behavior.…”
Section: Introductionmentioning
confidence: 99%